Accounting and tax principles for legal professionals - Walston-Dunham, Beth (Delmar Learning, 2008)
As the private practice law firm enters an increasingly competitive environment, firms must provide a wide variety of collateral services to clients to retain current business and to attract new clients. Because the law firm frequently has more knowledge than anyone else with respect to a client's financial status, tax assistance is a logical choice in terms of revenue generating services that can be offered to clients at a cost effective rate. Either an attorney or a paralegal can often provide tax assistance service. Additionally, because smaller firms often require support staff to function in dual roles, it is a perfect fit for the qualified paralegal to assist in basic accounting functions for the firm. This can be a much more cost-effective use of the paralegal's time and salary than to use the paralegal in a strictly clerical role. Accounting and Tax Principles for Legal Professionals will provide paralegal and law students with marketable skills to help assist in the financial management of the firm they join and to market these services to current and prospective clients.